Novel NHEJ1 pathogenic variant linked to severe combined immunodeficiency, microcephaly, and abnormal T and B cell receptor repertoires - Frizinsky, Shirly; Rechavi, Erez; Barel, Ortal; Lee, Yu Nee; Simon, Amos J.; Lev, Atar; Stauber, Tali; Adam, Etai; Somech, Raz (Frontiers in Pediatrics, 2022)
Background: During the process of generating diverse T and B cell receptor (TCR and BCR, respectively) repertoires, double strand DNA breaks are produced. Subsequently, these breaks are corrected by a complex system led by the non-homologous end-joining (NHEJ). Pathogenic variants in proteins involved in this process, including the NHEJ1 gene, cause severe combined immunodeficiency syndrome (SCID) along with neurodevelopmental disease and sensitivity to ionizing radiation. Objective: To provide new clinical and immunological insights on NHEJ1 deficiency, arising from a newly diagnosed patient with severe immunodeficiency. Methods: A male infant, born to consanguineous parents, suspected of having primary immunodeficiency underwent immunological and genetic work up. This included a thorough assessment of T cell phenotyping and lymphocyte activation by mitogen stimulation tests, whole exome sequencing (WES), TCR repertoire Vβ repertoire via flow cytometry analysis and TCR and BCR repertoire analysis via next generation sequencing (NGS). Results: Clinical findings included microcephaly, recurrent bacterial viral pneumonia and failure to thrive. Immune workup revealed lymphopenia, reduced T cell function and hypogammaglubolinemia. Skewed TCR Vβ repertoire, TCR gamma (TRG) repertoire and BCR repertoire were determined in the patient. Genetic analysis identified a novel homozygous missense pathogenic variant in XLF/Cernunnos: c.A580Ins.T; p.M194fs. The patient underwent a successful hematopoietic stem cell transplantation (HSCT). Conclusions: A novel NHEJ1 pathogenic variant is reported in a patient presented with SCID phenotype that displayed clonally expanded T and B cells. An adjusted HSCT was safe to ensure full T cell immune reconstitution.